2014
DOI: 10.1111/jre.12173
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of Toll‐like receptor 4 in healthy and diseased human gingiva

Abstract: TLR4, CD14 and MD-2, but not LBP, are expressed in human gingival keratinocytes and fibroblasts. The TLR4 expression level in the junctional epithelium appeared to be lowest within the periodontal epithelial barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 21 publications
3
25
0
1
Order By: Relevance
“…The presence of TLR2-expressing inflammatory cells described in PG and PC indicated that the disease is likely to be sustained by the immune system via reactions to bacterial antigens. 5 , 9 , 10 The same conclusions have been drawn in the only TLR4 study, 9 where TLR4 has been found to be constitutive and non-constitutively expressed in human epithelial cells; 13 , 20 , 21 , 23 , 29 , 30 no data are available about its expression in ERM and the epithelium cyst lining of PC. The present study examined its expression in PL by immunohistochemistry focusing on the epithelial compartment.…”
Section: Discussionsupporting
confidence: 56%
“…The presence of TLR2-expressing inflammatory cells described in PG and PC indicated that the disease is likely to be sustained by the immune system via reactions to bacterial antigens. 5 , 9 , 10 The same conclusions have been drawn in the only TLR4 study, 9 where TLR4 has been found to be constitutive and non-constitutively expressed in human epithelial cells; 13 , 20 , 21 , 23 , 29 , 30 no data are available about its expression in ERM and the epithelium cyst lining of PC. The present study examined its expression in PL by immunohistochemistry focusing on the epithelial compartment.…”
Section: Discussionsupporting
confidence: 56%
“…However, this question is investigated rather poorly to date. TLR2 and TLR4 agonists are of especial interest in our study, because these receptors play a key role in the progression of periodontal disease 24 , 25 and are activated by bacterial components such as lipopolysaccharide, peptidoglycan, lipoteichoic acid, bacterial lipoproteins. Therefore, in the present study we investigated the simultaneous effect of IFN-γ and TLR2 and TLR4 agonists on the expression of immunomodulatory protein IDO-1 and inflammatory mediators interleukin (IL) 6, IL-8, and MCP-1 in hPDLCS.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of HIF-1α may be modulated by TLRs and patern recognition in certain ways, since a TLR4 neutralizing antibody could atenuate such an efect from E. coli LPS. Moreover, the expression of TLR4, CD14, and MD-2 in both human gingival keratinocytes and ibroblasts is conirmed, and the TLR4 protein expression in periodontal epithelial compartments appeared diferent in vivo, indicating that LPS sensing in the dentogingival front in health could be heterogeneous in nature [92].…”
Section: Hif In the Periodontopathogen-host Cross Talkmentioning
confidence: 90%